TEACHING ENGLISH THROUGH INNOVATIVE TECHNOLOGIES (Zamonaviy dunyoda pedagogika va psixologiya, 2022)
The role and the effective usage of innovative technologies in teaching English are considered in this article. The Internet links, which areeffectively used during the lessons, are also shown here.